ANALISIS FINANSIAL USAHATANI AREN (Arenga Pinnata Meer) DI KAMPUNG SAKAQ TADA KECAMATAN MOOK MANNAR BULANTN KABUPATEN KUTAI BARAT - Yosia Yesi dan Abdul Kholik Hidayah (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Financial Analysis of Aren Farming (Arenga pinnata Meer) In Sakaq Tada Village, Mook Mannar Bulantn Sub District, West Kutai Regency.  This study aims to determine the cost of production , receipts or income and assess the feasibility of rubber farmers farming , identify problems and solutions . As consideration for the benefits to farmers in developing farming rubber plantation sector in the major commodities , materials enter the local government , particularly the technical agencies involved in the creation of programs and policies as well as consideration for researchers to further examine the issues related to this study. The research was conducted in the months of March to May 15, 2013 , where the research object in farming communities in the village of Aren by Tada Sakaq Mook Mannar District of West Kutai Bulant intensively seeking the sugar plant as its main commodity as well as the agency or agencies that can provide the data in this study. Sampling method , with respondents who have been determined ( purposive sampling ) the precession rate of 32 % , ie, 40 samples of respondents , taken 8 respondents representing each group . The data and information collected through questionnaire interview manufacture , documentation studies , observations in the field , then classified and tabulated according to type and production costs of the farm receipts purpose of this study , after the financial analyzed. The results obtained from this study are : ( 1 ) . Palm farm management in the community in the village of Tada Sakaq Mook Mannar District of West Kutai Bulant development to date has been running in its 10th year , has earned a profit of Rp . 27,811,200 , -/year , it is calculated based on the area of land per acre , ( 2 ) . In the palm farm management which covers 1 ha , it is known that the production costs incurred each year until the 10th year of Rp . 20,788,800 , - , ( 3 ) . Net Present Value ( NVP ) it can be seen that the cultivation of rubber at the interest rate of 8% , 12 % , 14 % and 18 % > 0 viable in the period beginning in the 15th , ( 4 ) . In line with the value of the Net Benefit Cost Ratio , which have > 1 year at the age of 15 plants ( 8 % interest rate , 10 % , 12 % , 14 % and 18 % ) , ( 5 ) . Gross value Net Benefit Cost Ratio calculated interest rate of 8% , 10 % , 12 % , 14 % and 18 % , indicating > 1 viable start year 9 , ( 6 ) . IRR calculation shows that rubber farming viable in the 9 -year concession period up to the 15.60 % discount rate , or interest rates below 16 % , ( 7 ) . In the financial aspect , palm cultivation is quite interesting because the value of Net B / C ratio > 1 and IRR values are still above the market rate , so that the management can still be developed .